2021
DOI: 10.3389/fonc.2020.601076
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Related Toxicities During Anti-GD2 Immunotherapy in High-Risk Neuroblastoma Patients

Abstract: The introduction of immunotherapy using an anti-GD2 antibody (dinutuximab, ch14.18) has significantly improved survival rates for high-risk neuroblastoma patients. However, this improvement in survival is accompanied by a substantial immunotherapy-related toxicity burden. The primary objective of this study was to describe treatment-related toxicities during immunotherapy with dinutuximab, IL-2, GM-CSF, and isotretinoin. A retrospective, single center analysis of immunotherapy-related toxicities was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Используемый нами режим терапии характеризовался сравнительно низкой токсичностью. Вероятно, меньшие, чем в сходных когортах [35], число и степень наиболее серьезных осложнений (гипотензия, синдром повышенной проницаемости капилляров, реакции гиперчувствительности) объяснялись особенностями режима введения препарата с применением 24-часовой инфузии [14,31], а также отсутствием в схеме лечения ИЛ-2 [15]. Препараты ИЛ-2 не применялись с учетом данных SIOPEN о сравнимой эффективности схемы лечения, не включающей в себя ИЛ-2 [36], при меньшей токсичности данной терапии [16].…”
Section: Discussionunclassified
“…Используемый нами режим терапии характеризовался сравнительно низкой токсичностью. Вероятно, меньшие, чем в сходных когортах [35], число и степень наиболее серьезных осложнений (гипотензия, синдром повышенной проницаемости капилляров, реакции гиперчувствительности) объяснялись особенностями режима введения препарата с применением 24-часовой инфузии [14,31], а также отсутствием в схеме лечения ИЛ-2 [15]. Препараты ИЛ-2 не применялись с учетом данных SIOPEN о сравнимой эффективности схемы лечения, не включающей в себя ИЛ-2 [36], при меньшей токсичности данной терапии [16].…”
Section: Discussionunclassified
“…There is very little information in the literature regarding visual disturbances in association with dinutuximab beta therapy [ 19 ], and this expert group believes that these events are under-reported in clinical studies. Ocular abnormalities, such as mydriasis and impaired accommodation, have also been reported with the humanised anti-GD2 antibody hu14.18K322A [ 20 ].…”
Section: Optimising Supportive Care For Children Receiving Dinutuximab Betamentioning
confidence: 99%
“…Neuropathic pain affects from 33% to 88% of pediatric patients undergoing dinutuximab infusion. Pain usually manifests as allodynia, which involves various regions of the body, especially the abdomen, extremities, back, and chest, and then spreads peripherally to the ankles and feet [ 18 , 32 , 37 , 42 , 43 , 44 ]. Anti-GD2 induced pain is characterized by mechanical allodynia without thermal hyperalgesia [ 23 ].…”
Section: Dinutuximab Induced Neuropathic Painmentioning
confidence: 99%
“…It usually begins within an hour from the start of dinutuximab beta infusion and is limited to the time of administration of this drug, ending shortly after the termination of the infusion; it usually occurs during the first infusion of the drug and decreases after each course [ 22 ]. A retrospective study on 26 patients affected by high-risk neuroblastoma who received dinutuximab based immunotherapy concluded that grade ≥3 (of a 1 to 5 scale) pain occurs in about 88% of patients during immunotherapy course 1, but in 42% of patients during course 5 [ 42 ].…”
Section: Dinutuximab Induced Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation